Architectural Works of J.H. Gevirtz after 1917 - Shabunina, Ekaterina I. (Actual Problems of Theory and History of Art, 2013)
The basic purpose of this article is the exploration of the final period of the architectural work of Jacob Gevirtz (1879‒1942) — the author of Judaic religious buildings and apartment houses projects in the pre-revolutionary Saint-Petersburg. After the revolution of 1917 the architect was engaged in the competitive design, research work and teaching. This period is considered on the basis of materials from the personal archive of J. Gevirtz.
Keywords: Jacob Gevirtz; soviet architecture; competitive design; constructivism